2018
DOI: 10.1021/acs.bioconjchem.8b00524
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Polyplexes with Post-Conjugated GALA Peptides Efficiently Target, Transfect, and Activate Antigen Presenting Cells

Abstract: Vaccines based on mRNA have emerged as potent systems to elicit CD8 T cell responses against various cancers and viral infectious diseases. The efficient intracellular delivery of mRNA molecules encoding antigens into the cytosol of antigen-presenting cells (APCs) is still challenging, requiring cell attachment, active uptake, and subsequent endosomal escape. Here, we report a facile approach for the formulation of peptide-functionalized mRNA polyplexes using copper-free click chemistry to promote presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 80 publications
0
67
0
2
Order By: Relevance
“…Various non-viral gene delivery vehicles made of cationic polymers or lipids with different modifications have been developed 27,43 . However, beyond the transfection of established cell lines, only few of them achieved robust gene delivery in primary cells 22,44 . The number of successful gene transfer systems is even more limited, when delivery of specific cargo such as mRNA is demanded 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Various non-viral gene delivery vehicles made of cationic polymers or lipids with different modifications have been developed 27,43 . However, beyond the transfection of established cell lines, only few of them achieved robust gene delivery in primary cells 22,44 . The number of successful gene transfer systems is even more limited, when delivery of specific cargo such as mRNA is demanded 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Rationally designed targeting approaches, such as including ligands to tissue-specific receptors, are an alternative strategy. 94 Recently, Lou et al 95 reported an in vitro active targeting of sialic acid-ended glycoproteins on the surface of dendritic cells, mediated by a 30-amino-acid synthetic peptide with glutamic acid-alanine-leucine-alanine (GALA) repeats conjugated to polyplex carrying EGFP-mRNA. However, any opsonization on the LNPs forming a protein corona can be detrimental to active-targeting strategies, due to masking of the targeting ligands.…”
Section: Biodegradability and Targeting Issues With Non-viral Vectorsmentioning
confidence: 99%
“…In this section, we discuss different delivery strategies and types of carriers used for mRNA-based protein therapy. 95,96 Intramyocardial injection of modified RNA encoding human VEGF-A, complexed with RNAiMAX, has been reported to improve heart function and long-term survival of mice with myocardial infarction. 101 Turnbull et al 102 compared intracoronary administration and direct myocardial injection of mRNA formulated into the LNPs (C14-113) in rodents and pigs, showing that the latter led to higher cardiac and lower off-target mRNA expression.…”
Section: Biodegradability and Targeting Issues With Non-viral Vectorsmentioning
confidence: 99%
“…For pegylation, BCN-PEG (BCN-PEG-COOH) or BCN-PEG-cRGD as added to the polyplexes at the amount of PEG equivalent to 60 mol% of an azide of the polymer used for preparing polyplexes and left to react for 2 h at room temperature. This ratio was selected based on our prior studies, in which we investigated the optimal post-PEGylation ratio for RNA polyplexes [25,34]. For freezedrying of the polyplexes, sucrose was added to the polyplex formulation to a final concentration of 5% before snapfreezing in liquid nitrogen.…”
Section: Characterization Of Polymermentioning
confidence: 99%
“…The resulting polymers formed small siRNA polyplexes through both polycation electrostatic interaction and siRNA and hydrophobic interaction via cholesterol. Subsequently, these polyplexes were post-modified with PEG-cRGD modified with bicyclo[6.1.0]nonyne (BCN) using copper-free click chemistry to shield surface charge and enable ligand-mediated cell binding and uptake [25,34]. In vitro experiments showed enhanced cellular uptake of PEG-cRGD modified polyplexes, which in turn resulted in improved transfection efficiency as compared to non-PEGylated particles.…”
Section: Introductionmentioning
confidence: 99%